Analysis of multiple haloarchaeal genomes suggests that the quinone‐dependent respiratory nitric oxide reductase is an important source of nitrous oxide in hypersaline environments. Issue 6 (9th November 2017) - Torregrosa‐Crespo, Javier; González‐Torres, Pedro; Bautista, Vanesa; Esclapez, Julia M.; Pire, Carmen; Camacho, Mónica; Bonete, María José; Richardson, David J.; Watmough, Nicholas J.; Martínez‐Espinosa, Rosa María
Summary: Microorganisms, including Bacteria and Archaea, play a key role in denitrification, which is the major mechanism by which fixed nitrogen returns to the atmosphere from soil and water. While the enzymology of denitrification is well understood in Bacteria, the details of the last two reactions in this pathway, which catalyse the reduction of nitric oxide (NO) via nitrous oxide (N2 O) to nitrogen (N2 ), are little studied in Archaea, and hardly at all in haloarchaea. This work describes an extensive interspecies analysis of both complete and draft haloarchaeal genomes aimed at identifying the genes that encode respiratory nitric oxide reductases (Nors). The study revealed that the only nor gene found in haloarchaea is one that encodes a single subunit quinone dependent Nor homologous to the qNor found in bacteria. This surprising discovery is considered in terms of our emerging understanding of haloarchaeal bioenergetics and NO management.